La política exterior peruana hacia Israel y Palestina - Kahhat Kahatt, Farid (El Colegio de México A.C., 2024)
To understand Peru’s policy towards the Middle East, it is necessary to grasp the overall orientation of its foreign policy, which stems from the fact that Peru is a middle-income country with a peripheral position in the international system and tends to prioritize multilateralism as a means to defend its interests. In other words, it seeks to act within the framework of international law and institutions to protect its interests jointly with other countries that occupy a similar position in the international system. This, in turn, creates tensions between the defense of multilateralism and international law on one hand, and the need to preserve good relations with certain states on the other, which has been evident in the aftermath of the October 7, 2023 attack. Fluctuations in Peru’s foreign policy have been more influenced by changes in U.S. policy, translating into greater relative autonomy.